Lower physical activity is associated with daytime sleepiness in children aged 9–12 years. (September 2019) - Isa, Tsunenori; Sugimoto, Taiki; Murata, Shunsuke; Tsuboi, Yamato; Ebina, Aoi; Kondo, Yuki; Torizawa, Kohtaroh; Okumura, Maho; Shigemoto, Chihiro; Matsuda, Naoka; Misu, Shogo; Ono, Rei
This study clarified the prevalence of daytime sleepiness in fourth-, fifth-, and sixth-grade children and examined the association between physical activity (PA) and daytime sleepiness in children aged 9–12 years. This cross-sectional study included 314 children (mean age ± standard deviation: 10.5 ± 1.0 years; male: 52.9%) enrolled in two public elementary schools in Kobe, Japan. PA was assessed using the Physical Activity Questionnaire for Older Children. The outcome was self-reported daytime sleepiness. The prevalence of daytime sleepiness in fourth-, fifth-, and sixth-grade children were 10.8%, 25.2%, and 28.6%, respectively. In univariate analysis, subjects with reported daytime sleepiness had lower PA levels than those without daytime sleepiness (odds ratio (OR) = .67; 95% confidence interval (CI) = .47–.95). Multiple logistic regression analysis demonstrated that lower PA was significantly associated with daytime sleepiness after adjusting for multiple confounders (OR = .54; 95% CI = .37–.81). The prevalence of daytime sleepiness in fifth and sixth grades was higher than fourth grade. Furthermore, this study clarified the significant association between PA and daytime sleepiness and suggested that PA could be one of the factors to prevent daytime sleepiness in children aged 9–12 years.